Proximate composition, total phenolics content and antioxidant activities of microalgal residue from biodiesel production - Pamon Pumas (2018)
In biodiesel production, lipid is extracted from algal biomass but some beneficial substances may remain in its residue. In this study proximate composition, total phenolics content and antioxidant activities of a microalgal residue after lipid extraction were determined. It was found that the residue has a high protein content and the hot aqueous extract of the residue is high in both the phenolics content and the level of antioxidant activities. © 2014 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.